2020
DOI: 10.1159/000507311
|View full text |Cite
|
Sign up to set email alerts
|

Application of the International System for Reporting Serous Fluid Cytopathology (ISRSFC) on Reporting Pericardial Effusion Cytology

Abstract: Introduction: The International System for Reporting Serous Fluid Cytopathology (ISRSFC) has recently been announced. Pericardial effusion (PE) is a clinical manifestation of a large variety of both neoplastic and non-neoplastic conditions. Herein, we have applied the ISRSFC on reporting PE cytopathology and report our experience in a large academic institution. Method and Materials: After the Institutional Research Board approval, the electronic pathology database of a large academic institution was queried f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 18 publications
11
58
4
Order By: Relevance
“…(B) Boxplot of the time interval between the first diagnosis of a malignant pericardial effusion and the last follow-up date according to the primary site category in the pleural fluid of between 0.6% and 1.6% 21 and that the incidence of AUS in PE cases would be increased. However, the incidence of AUS has been reported from 1.6% to 9.6% 9,14,17,18 including our present study. Our study also found a relatively high incidence of AUS due to our categorization of "atypical cells, favor reactive".…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…(B) Boxplot of the time interval between the first diagnosis of a malignant pericardial effusion and the last follow-up date according to the primary site category in the pleural fluid of between 0.6% and 1.6% 21 and that the incidence of AUS in PE cases would be increased. However, the incidence of AUS has been reported from 1.6% to 9.6% 9,14,17,18 including our present study. Our study also found a relatively high incidence of AUS due to our categorization of "atypical cells, favor reactive".…”
Section: Discussioncontrasting
confidence: 54%
“…Prior large-scale studies involving PE cytology were reviewed 3,9,[14][15][16][17][18][19][20] and are summarized in Table 5. In brief, PE has an incidence of 1.5% to 4.5% among the total body fluids including pleural, pericardial, and peritoneal fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent publications have looked at the risk of malignancy (ROM) for each of these categories. They have shown that values vary between affected cavities [ 5 , 6 , 17 , 18 , 19 , 20 , 21 , 22 ]. Most studies, however, were published before the development and implementation of TIS, with few exceptions [ 5 , 6 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, only a limited number of studies have supported the use of a particular terminology for serous fluid cytology 6‐11 . In this study, we applied TIS recommendations for reporting the cytological diagnosis of pleural effusion.…”
Section: Introductionmentioning
confidence: 99%